Rubber, coffee and cocoa polyculture economic and environmental viability - Cruz González Belén; Jarquín Gálvez Ramón; Ramírez Tobias Hugo Magdaleno (Revista Mexicana de Ciencias Agrícolas, 2018)
Polyculture in general have received increasing attention by the apparent advantages in the utilization of space and environmental services offered. However, it is known that not all combinations of crops can be economically and environmentally competitive, for this reason the aim of this study was to evaluate in 2008, the economic and environmental viability of four economically important crops and the existing possible combinations of these in the town of Huehuetán, Chiapas, Mexico. Economic, physical, chemical, and biological indicators were evaluated using multivariate statistical analysis of main components and the t-student test. We found that, the polyculture robusta coffee- cocoa and rubber-cocoa obtained a LER of 1.33 and 1.13 respectively and a B/C relation of 2.59 and 1.89, so they were the most economically viable. The polyculture rubber-Arabic coffee presented interspecific interference characteristics. The rubber as monoculture as well as the polyculture rubber-cocoa was the most economically and environmentally viable, significantly exciding in each indicator and to the correction possibilities of limiting factors such as pH and the amount of light that the producers have.